1993
DOI: 10.2307/1940072
|View full text |Cite
|
Sign up to set email alerts
|

Life and Death in Moving Fluids: Hydrodynamic Effects on Chemosensory‐Mediated Predation

Abstract: Previous studies in taxonomically diverse marine animals have established the general existence, and importance, of the olfactory sense in a wide variety ofbehavioral processes. Evidence suggests that the sense of smell mediates predatory search in many marine animals. Past investigations have not, however, been designed to link either the degree of successful olfactory-mediated search or guidance mechanisms with the hydraulic environment in which predatory activities naturally take place. In an effort to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
236
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(247 citation statements)
references
References 64 publications
8
236
3
Order By: Relevance
“…Other bivalves (e.g., mussels) also use chemical cues to detect predators and respond by changing their morphology (e.g., Leonard et al, 1999) or behavior (e.g., Cote ' and Jelnikar, 1999). Previous studies have shown that blue crabs depend on chemical cues to locate clam prey (Weissburg and Zimmer-Faust, 1993;Finelli et al, 2000;Weissburg et al, 2002). The modulation of the blue crab-clam predatory interaction by chemicals is perhaps unsurprising given that the water in our study area is extremely turbid, and chemical cues are likely the only signals that can be detected from a distance in this habitat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other bivalves (e.g., mussels) also use chemical cues to detect predators and respond by changing their morphology (e.g., Leonard et al, 1999) or behavior (e.g., Cote ' and Jelnikar, 1999). Previous studies have shown that blue crabs depend on chemical cues to locate clam prey (Weissburg and Zimmer-Faust, 1993;Finelli et al, 2000;Weissburg et al, 2002). The modulation of the blue crab-clam predatory interaction by chemicals is perhaps unsurprising given that the water in our study area is extremely turbid, and chemical cues are likely the only signals that can be detected from a distance in this habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Blue crabs are also a threat to adult clams, as they can nip their siphons and decrease their feeding efficiency, growth, and fecundity (Peterson, 1986;Coen and Heck, 1991;Irlandi, 1994). Clams release attractive chemicals into the water as they feed, and blue crabs follow these waterborne chemical odor plumes to locate their clam prey (Weissburg and Zimmer-Faust, 1993;Weissburg et al, 2002). Irlandi and Peterson (1991) found that clams responded to the presence of predators by reducing their feeding time and hypothesized that feeding reductions would make clams less apparent to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Successful longdistance navigation by means of olfaction has been found in birds (Gagliardo et al 2013), fish (Keefer and Caudill 2013) and crabs (Weissburg and Zimmer-Faust 1994). Although olfaction is a well-developed sense in many marine benthic invertebrates, it is much less accurate as a directional homing cue in the presence of boundary layer turbulence (Weissburg and Zimmer-Faust 1993), which can be found close to large structures like coral reefs. At close quarters, visual detection can provide the animals with a reliable cue and is believed to be used by crown-ofthorns starfish to settle on reefs ).…”
Section: Finding Coral Reefsmentioning
confidence: 99%
“…Asteroids, in contrast to the above predators, are slow-moving, nonvisual predators which usually use chemodetection to search for prey (Sloan & Campbell 1982, Rochette et al 1994. Crevice use may also render Iceland scallops more difficult to detect by asteroids because odour plumes originating from scallops in crevices are likely weaker and distorted by turbulence near the bottom (Weissburg & Zimmer-Faust 1993).…”
Section: Effect Of Refuge Use On Vulnerability To Predatorsmentioning
confidence: 99%